Marketing Strategy in Managing Hospital Patient Satisfaction - Wawan Novianto; Firdaus; Ali M Zebua (Formosa Journal of Applied Sciences, 2022)
The purpose of this research is to menganaisis the influence of the value of customer and Patient Satisfaction Marketingterhadap Experiential BPJS MMC Hospital in Jambi. Sample research that used as many as 100 people respondents, where data from samples collected using a questionnaire and then analyzed by Structural Equation Modelling (SEM) component-based partial least squares path modeling (PLS-SEM). Based on research results that have been obtained, it can be inferred, the value of a customer is reflected by the dimensions of emotional value, social value, performance, value, and price value of moneysecara partial positive and significant effect against patient satisfaction BPJS MMC Hospital in Jambi. Marketingyang is reflected by the experiential dimension of sense, feel, think, and actsecara partial positive and significant effect against patient satisfaction BPJS MMC Hospital in Jambi. Collectively the value of customers and experiential marketingmemiliki influence on patient satisfaction BPJS MMC Hospital in Jambi.